On-farm conservation of tropical fruit tree diversity: roles and motivations of custodian farmers and emerging threats and challenges - Sthapit, B.R.; Vasudeva, R.; Rajan, S.; Sripinta, P.; Reddy, B.M.C.; Arsanti, I.W.; Idris, S.; Lamers, H.; Ramanatha Rao, V. (International Society for Horticultural Science, 2015)
Agricultural biodiversity is shrinking very fast. That said, there are still a few farmers who continue to maintain, innovate and disseminate fruit tree diversity in their home gardens and orchards. The study was conducted in 36 communities of India, Indonesia, Malaysia and Thailand to find out why some farmers do maintain rich fruit tree diversity whereas many do not. The study also aims to answer the following research questions: What conservation practices do farmers do and what are the motivations for their efforts? What are characteristics of such farmers and what are key challenges? Participatory four cell method was carried out amongst the potential custodian farmers, followed by key informant survey and field validation. We found that quite a few farmers maintain rich diversity with few rare and unique fruit tree species or varieties and are mainly driven by conservation ideology. The characteristics of such custodian farmers were identified and found to differ in their functions and motivations. Some functions of custodian farmers are critical for on-farm conservation of tropical fruit tree diversity. The paper also recommends how to consolidate their roles as conserver, innovator and promoter of local fruit tree diversity.